DISCUSSING HEALTH PROMOTION AND DISEASE PREVENTION CONCEPTS (Fiep Bulletin - online, 2013)
This bibliographical study aims to establish a reflection upon conceptual delimitation of health promotion and disease prevention concepts revealing how close and distant they are from one another. Through this reflection it is relevant to emphasize how necessary it is for health professional to enlarge their view regarding health/disease processes especially at the implementation and development point of actions towards health thus seeking to promote health with a focus broader than the one restricted to diseases with power to value and reinforce responsibilities and rights for individuals and communities concerning their own health meeting principles proposed by Ottawa Charter.
Keywords: health promotion; disease prevention; health professional